1996
DOI: 10.1007/bf00126935
|View full text |Cite
|
Sign up to set email alerts
|

Indian cucumber germplasm and challenges ahead

Abstract: Cucumbers (Cucumis sativus) are considered to be native to India. The germplasm of cultivated and wild relatives is shown to grow in very diverse agroecological conditions of the country. The north-eastern region is shown to hold special significance for wild and cultivated germplasm. The disease and specific adaptation characters are pointed out. Future scope for commercial growing and research needs are emphasised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Although these botanical varieties are cross-compatible and var. hardwickii possesses several economically important traits (e.g., multiple and sequential fruiting habit [35] ; downy mildew resistance [36] ; root-knot nematode resistance [37] ; cucumber mosaic virus [38] ), their introgression into elite commercial germplasm has been difficult. If genes controlling such traits are located in the regions with chromosomal variation, then fixation of positive alleles in commercial types would likely be complicated.…”
Section: Discussionmentioning
confidence: 99%
“…Although these botanical varieties are cross-compatible and var. hardwickii possesses several economically important traits (e.g., multiple and sequential fruiting habit [35] ; downy mildew resistance [36] ; root-knot nematode resistance [37] ; cucumber mosaic virus [38] ), their introgression into elite commercial germplasm has been difficult. If genes controlling such traits are located in the regions with chromosomal variation, then fixation of positive alleles in commercial types would likely be complicated.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to these resistance sources, Cucumis sativus var. hardwickii is also reported to offer resistance to downy mildew (Sharma and Hore 1996) and root-knot nematodes (Walters et al 1999) along with multiple and sequential fruiting habit (Host and Lower 1978). Thus this species is a valuable genetic source for the improvement of multiple traits in cucumber.…”
Section: Inheritance Of CMV Resistancementioning
confidence: 95%
“…hardwickii R. Alef. a native of Sub-Himalayan region and considered to be the wild progenitor of cucumber (Deakin et al 1971) has been reported to possess resistance to downy mildew (Sharma and Hore 1996) and root-knot nematodes (Walters et al 1999) apart from possessing multiple and sequential fruiting habit (Horst and Lower 1978). However, utilization of this species as a resistant source against CMV and the genetics of its resistance have not been reported so far.…”
Section: Introductionmentioning
confidence: 98%
“…agrestis (Naud.) Pangalo are also reported to possess drought tolerance (Sharma and Hore 1996). Therefore, further characterization of these accessions with respect to various traits of economic importance will help in validating the sources of useful genes in improvement of cucumber and muskmelon.…”
Section: Germplasm Conservation and Potential Usesmentioning
confidence: 99%
“…hardwickii (Royle) Alef., has both multiple lateral branching and sequential fruiting characters and has shown potential for increasing fruit yields in C. sativus. Besides this, it is also a valuable source for different characters such as resistance to cucumber green mottle mosaic virus (Sharma and Hore 1996), root-knot nematode (Walters et al 1997), downy mildew and scab diseases (Staub and Palmer 1987). C. prophetarum is reported to be resistant to powdery mildew, corky-root (Pitrat and de Vaulx 1979), root-knot nematode (Sharma and Hore 1996) and cucumber vein yellowing virus (Marco et al 2003).…”
Section: Germplasm Conservation and Potential Usesmentioning
confidence: 99%